Overexpression of SNF4 and deletions of REG1- and REG2-enhanced maltose metabolism and leavening ability of baker's yeast in lean dough. (1st September 2018) - Lin, Xue; Zhang, Cui-Ying; Meng, Lu; Bai, Xiao-Wen; Xiao, Dong-Guang
Abstract: Maltose metabolism of baker's yeast ( Saccharomyces cerevisiae ) in lean dough is suppressed by the glucose effect, which negatively affects dough fermentation. In this study, differences and interactions among SNF4 (encoding for the regulatory subunit of Snf1 kinase) overexpression and REG1 and REG2 (which encodes for the regulatory subunits of the type I protein phosphatase) deletions in maltose metabolism of baker's yeast were investigated using various mutants. Results revealed that SNF4 overexpression and REG1 and REG2 deletions effectively alleviated glucose repression at different levels, thereby enhancing maltose metabolism and leavening ability to varying degrees. SNF4 overexpression combined with REG1 / REG2 deletions further enhanced the increases in glucose derepression and maltose metabolism. The overexpressed SNF4 with deleted REG1 and REG2 mutant Δ REG1 Δ REG2  + SNF4 displayed the highest maltose metabolism and strongest leavening ability under the test conditions. Such baker's yeast strains had excellent potential applications.